In Vivo Priming of Peritoneal Tumor-Reactive Lymphocytes With a Potent Oncolytic Virus for Adoptive Cell Therapy - Giehl, Esther; Kosaka, Hiromichi; Liu, Zuqiang; Feist, Mathilde; Kammula, Udai S.; Lotze, Michael T.; Ma, Congrong; Guo, Zong Sheng; Bartlett, David L. (Frontiers in Immunology, 2021)
Adoptive cell therapy (ACT) using autologous tumor infiltrating lymphocytes (TIL) achieves durable clinical benefit for patients from whom these cells can be derived in advanced metastatic melanoma but is limited in most solid tumors as a result of immune escape and exclusion. A tumor microenvironment (TME) priming strategy to improve the quantity and quality of TIL represents an important tactic to explore. Oncolytic viruses expressing immune stimulatory cytokines induce a potent inflammatory response that may enhance infiltration and activation of T cells. In this study, we examined the ability of an attenuated oncolytic vaccinia virus expressing IL15/IL15Rα (vvDD-IL15/Rα) to enhance recovery of lavage T cells in peritoneal carcinomatosis (PC). We found that intraperitoneal (IP) vvDD-IL15/Rα treatment of animals bearing PC resulted in a significant increase in cytotoxic function and memory formation in CD8+ T cells in peritoneal fluid. Using tetramers for vaccinia virus B8R antigen and tumor rejection antigen p15E, we found that the expanded population of peritoneal CD8+ T cells are specific for vaccinia or tumor with increased tumor-specificity over time, reinforced with viral clearance. Application of these vvDD-IL15/Rα induced CD8+ T cells in ACT of a lethal model of PC significantly increased survival. In addition, we found in patients with peritoneal metastases from various primary solid tumors that peritoneal T cells could be recovered but were exhausted with infrequent tumor-reactivity. If clinically translatable, vvDD-IL15/Rα in vivo priming would greatly expand the number of patients with advanced metastatic cancers responsive to T cell therapy.